Uni-Corn Co. - Mohd Fikri Lai, Abdul Aziz Lai; Majok, Puja; Mintik, Martin; Joibi, Nur Rasyidah; Maitin, Nurul Hidayahtulrahmah (2012)
The name of our company is Uni-Corn Company. It is a partnership business consists of five contributors. Uni-Corn stands for Universal Corn as we are targeting to expand our business throughout the world in long term achievement. Growing, Processing and Distribution of Corn and Corn Kernel are something new to our targeted region which is in the state of Sabah. This is because there is only one district which is in Tuaran who run this corn business in large-scale. At first, we realize that the demand for corn-based product such as mayonnaise steam corn kernel, steam corn, grilled corn and even frozen corn kernel has increased in Sabah. However, most of the stock was imported from Peninsular Malaysia to fulfill the demand of local (Sabah) market that makes the price mark up for certain level. We have confident that if we manage to produce corn in Sabah itself, the price will be much lower than corn imported from Peninsular Malaysia. Add up with the fertilize soil in Kundasang, we sure able to produce higher quality of corn product. The idea then becomes action when five of us agreed to become partner and become entrepreneur in this business. Hence, we believe that as a pioneer of largescale producer and distributor of corn product which located in the middle of Sabah (Kundasang), we will able to strike the market from East to West of Sabah, each and every town.